2003
DOI: 10.1002/ejoc.200300368
|View full text |Cite|
|
Sign up to set email alerts
|

Pyridyl Phosphinites and Pyridyl Phosphites from Chiral Pyridyl Alcohols — A Modular Approach

Abstract: Chiral arylated pyridyl alcohols, pyridyl phosphinites and pyridyl phosphites were prepared by Suzuki arylation and/or O-functionalization with a chlorodiarylphosphane or a chlorodiarylphosphite of chiral 2-bromo-6-(1-hydroxyalkyl)pyridines or 2-(1-hydroxyalkyl)pyridines, with the chirality originating from the chiral pool. The pyridyl alcohols were assessed as catalysts for the addition of diethylzinc to benzaldehyde and the P,N-ligands were employed in the palla-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…This compound is only secondary ortho alcohol proton sponge presently known [6,7], whose 1 H NMR spectrum in CDCl 3 has a two-proton OH group signal at δ 5.72 ppm. We should note that this shift is similar to the average chemical shift of OH groups in chelated (δ 6.5-7.7 ppm) [9,10] and nonchelated pyridylcarbinols (δ 3.25-4.45 ppm) [11]. Both these findings suggest that alcohol 9 exists in solution as a pair of degenerate forms 9a and 9b, which rapidly interconvert on the NMR time scale.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…This compound is only secondary ortho alcohol proton sponge presently known [6,7], whose 1 H NMR spectrum in CDCl 3 has a two-proton OH group signal at δ 5.72 ppm. We should note that this shift is similar to the average chemical shift of OH groups in chelated (δ 6.5-7.7 ppm) [9,10] and nonchelated pyridylcarbinols (δ 3.25-4.45 ppm) [11]. Both these findings suggest that alcohol 9 exists in solution as a pair of degenerate forms 9a and 9b, which rapidly interconvert on the NMR time scale.…”
supporting
confidence: 67%
“…We took into consideration that chelation involving the NMe 2 group shifts the OH signal to 10.5-10.7 ppm [6,7], while chelation involving the 2-aza group shifts this signal to 6.0-7.7 ppm [9,10]. In the absence of chelation due to the formation of aggregated species, within which the proton is rapidly exchanged, the OH group peak in CDCl 3 solution, as a rule, is not seen or is found at δ 3.5-4.5 ppm; the OH group gives a doublet at δ 5.1-5.7 ppm in DMSO-d 6 due to decomposition of the aggregated species [6,7,11].…”
mentioning
confidence: 98%
“…We have also demonstrated that the pyridylalcohols obtained in this way can be smoothly converted into pyridine-phosphinites. 11 Thus, reactions of 2a-d with diphenylchlorophosphine followed by treatment with BH 3 -SMe 2 proceeded efficiently, providing protected ligands 1a-d (43%, 62%, 77% and 60%, respectively). Due to the modular nature of the synthetic procedure, ligand structures are easily varied not only by employing different natural products and differently substituted pyridine derivatives, but also by using different chlorophosphines.…”
Section: Preparation Of Ligandsmentioning
confidence: 91%
“…Starting from methyl (S)-2-methoxy-2-phenylacetate (methyl mandelate), an analogous procedure afforded 2c as a single isomer in 49% yield over two steps when the reduction was performed at low temperature (-78 °C). 11 The corresponding reaction with 2-bromo-6-lithiopyridine gave a ketone which was reduced in situ to a single isomer (23% over two steps). Suzuki coupling with phenylboronic acid gave 2d (85%).…”
Section: Preparation Of Ligandsmentioning
confidence: 99%
“…90 However, probably the alkyllithium-promoted bromo-lithium exchange has been the most frequently employed methodology when 2-lithiated pyridines have been required for synthetic purposes. Thus, 2-lithiopyridine, obtained by treatment of 2-bromopyridine with nbutyllithium, has been used in addition reactions to ketones, 91 nitriles, 92 amides 93 and the ring-opening of sulfamates. 94 Other substituted 2-pyridyllithium reagents have been obtained similarly and used recently in addition reactions to aldehydes, 95 Weinreb amides, 96 DMF, 97 and acyl chlorides, as in the reaction of the organolithium 30, prepared from 2-bromopyridine 29 by the typical exchange procedure, with pivaloyl chloride (Scheme 10).…”
Section: Aromatic Six-membered Ringsmentioning
confidence: 99%